Synthesis of porphyrins as precursors to PAMAM dendrimers and their metal chelating properties - Hernandez-Ramirez, Raquel Eunice; Lijanova, Irina Victorovna; Likhanova, Natalya Victorovna; Olivares-Xometl, Octavio; Lartundo-Rojas, Luis (European Journal of Chemistry, 2016)
Novel meso-porphyrins were synthesized via microwave assistance and implemented as centers to polyamide amine (PAMAM) dendrimers. The molecular structures of the porphyrins were characterized by UV-Vis, 1H and 13C NMR spectroscopy. In addition, porphyrin-PAMAM dendrimers were characterized by 1H and 13C NMR spectroscopy. The molecular weight of the prepared dendrimers were confirmed by MALDI-TOF mass spectrometry. These porphyrin-core-PAMAM-modified dendrimers were used as templates to form Ag0 species and doped nylon membranes, using the XPS technique to confirm the chemical reduction of the metal cation.